Análise de polimorfismos e metilação de DNA nos genes DNMT1, DNMT3A e DNMT3B em pacientes oncopediátricos com mucosite oral quimioinduzida - Souza, Beatriz Fernandes de (2023)
Chemoinduced oral mucositis is a common adverse effect of antineoplastic treatment and is characterized by an inflammatory condition that affects the mucous membranes. In addition to presenting high morbidity, the presence of severe symptoms can result in the interruption of antineoplastic therapy, affecting both the quality of life of patients and the treatment prognosis. The use of antimetabolite drugs, such as methotrexate (MTX), and individual genetic variations are considered risk factors for the onset of mucositis. Based on this, this study aimed to investigate the association between the presence of single-base genetic polymorphisms (SNPs) and the methylation profile in genes that belongs to the DNA methyltransferases (DNMTs) family with the occurrence and severity of oral mucositis in children and adolescents with hematological malignancies and treated with methotrexate, in order to verify whether this family of genes can be used as a biomarker for the onset of inflammation or exposure to MTX. The assessment of oral conditions was performed using the modified Oral Assessment Guide. Demographic, clinical, hematological and biochemical data were obtained from hospital records. The genomic DNA of the epithelial cells of the oral mucosa was used for the analysis of the polymorphisms of DNMT1 (rs2228611), DNMT3A (rs7590760) and DNMT3B (rs6087990), (n=102), through the technique of PCR-Restriction Fragment Length Polymorphism (PCR -RFLP), and to determine the DNA methylation profile (n=85), Methylation Specific PCR (PCR-MSP) was used. The sample consisted of healthy and pediatric oncopediatric patients aged between 4 and 19 years and the most common neoplasm was Acute Lymphoblastic Leukemia. Of the 102 patients, 84.3% developed oral mucositis, and of these, 53.1% had severe symptoms of the disease. The allele and genotype frequencies of SNPs did not reveal differences between patients with and without oral mucositis. Regarding the analyzes of the epigenetic profiles, an increase in the frequency of methylation for DNMT1 was detected in patients recovered from mucositis. Combined analyzes of the hematological and biochemical data with the genetic and epigenetic profiles of the patients revealed that: both the methylated profile of DNMT3A associated with the CC genotype (SNP rs7590760) and the unmethylated profile of DNMT3B associated with the CC genotype (SNP rs6087990) are associated with higher creatinine values. Thus, we conclude that the DNMT1 methylation profile is associated with the post-mucositis period and the genetic and epigenetic profiles of DNMT3A and DNMT3B are associated with creatinine levels.